ANALISIS STRATEGI SISWA KELAS IX SMP DALAM MENYELESAIKAN MASALAH ALJABAR - Nihayatus Sa’adah; Siti Faizah (Prodi Pendidikan Matematika FKIP Universitas Madura, 2022)
One skill that students can develop through the mathematics learning process in the classroom is problem solving skill. Polya said that one of four mathematics problem solving steps was planning. In the planning step, there was a strategy that can be used by students to solve the problem. This qualitative research aimed to analyze the third grade of junior high school student's strategy in solving algebraic problem. The subjects in this research were three students with high mathematics ability and three students with medium mathematics ability. The data were collected by using primer and secondary instruments. The primer one was the researcher and the secondary one was algebraic problem solving sheet. The result of the research showed that students could use different strategies when solving the same algebraic problem. Those strategies were changing point of view and making simple analogy, reasoning logically, working backwards, and organizing data.